COMPARISON OF NASAL PATENCY FOLLOWING SUBMUCOSAL DIATHERMY OF INFERIOR TURBINATE VERSUS INFERIOR TURBINECTOMY: Diathermy of Inferior Turbinate Versus Inferior Turbinectomy - Nawaz, Faiz-ul-Hassan; Jawaid, Arfat; Bashir, Sheraz (Pakistan Armed Forces Medical Journal, 2014)
Objective: To compare the nasal patency following sub mucosal diathermy (SMD) of inferior turbinate and inferior turbinectomy (IT).Study Design: Randomized controlled trial.Place and Duration of Study: Department of ENT Combined Military Hospital Rawalpindi. Study was completed in one year from 15th September 2009 to 15th September 2010.Subjects: Total 160 patients with symptomatic inferior turbinate hypertrophy were included in the study. Patients were randomly divided into two groups of 80 each using random numbers table. Group A underwent submucosal diathermy (SMD) of inferior turbinate where as Group B underwent inferior turbinectomy (IT). Postoperative nasal patency was judged after 03 weeks by visual analog scale (VAS).Results: Both the groups are comparable with respect to age and gender. Post-operative nasal patency is significantly better in group B as compared to group A.Conclusion: IT is a more effective method to improve nasal patency as compared to SMD in case of inferior turbinate hypertrophy.